“Why It's Different?”: Hierarchies of (Non-) Belonging in German Refugee Categorizations - Emily Frank (Journal of Immigrant & Refugee Studies Journal of Immigrant & Refugee Studies, 2025)
Migrants' perceptions of belonging are shaped by the social policies with which they are received by the state. In Germany, policies grant refugees different levels of labor market access according to legal status, a hierarchical system also referred to as differential inclusion. This study compares perceptions and experiences of these labor market policies and discourses among refugees with four legal statuses. Refugees with the most precarious legal status are largely barred from the labor market, leading them to experience severe exclusion and pushing them into liminal spaces of existence. While recognized refugees may be able to work, racialized discourses about their deservingness create conditional and limited senses of belonging..Finally, refugees often themselves observe these hierarchies, reinforcing feelings of exclusion. Results demonstrate how the hierarchies present in policies create a stratified system of differential non-belonging. Overall, the article sheds light on how differential inclusion of refugees also results in hierarchized experiences of differential (non-)belonging.
Keywords: 320; Immigrants; refugees; social policy; Germany; belonging; labor market; differential inclusion